Fetal Right Ventricular Diverticulum Detected by Prenatal Ultrasound Screening. (12th October 2016) - Katsura, Daisuke; Hayashi, Kaori; Tsuji, Shunichiro; Ono, Tetsuo; Ishiko, Akiko; Takahashi, Kentaro; Murakami, Takashi
Abstract : Prenatal ultrasound screening has allowed for the detection of in utero cardiac abnormalities. Specifically, distinction is possible between ventricular diverticula and aneurysms, which is important because each condition has a different clinical outcome. We report the case of a 35-year-old, gravida 1, para 1 woman, with no significant past medical history, who underwent routine prenatal ultrasound screening at 32 weeks' gestation. A four-chamber ultrasound of the fetal heart combined with M-mode echocardiography showed abnormal dilatation of the right ventricular chamber measuring 2.2 cm × 1.0 cm but with normal contractility. Delivery was performed at full term by cesarean section, and a right ventricular diverticulum was confirmed by postnatal cardiac computed tomography. The baby developed normally with no cardiac sequelae during followup. This case demonstrates the importance of making a correct diagnosis of ventricular diverticula by prenatal ultrasound when abnormal dilatation of the fetal ventricle is identified during routine screening. Because evaluating the wall contractility by M-mode ultrasound leads to evaluating whether it has the myocardium, we conclude that M-mode echocardiography is effective for the purpose of prenatal cardiac diagnosis and can distinguish between ventricular aneurysms and functioning ventricular diverticula.